Recent advances in coeliac disease - Ciclitira, Paul J (Clin Med (Lond), 2003)
Coeliac disease, or gluten-sensitive enteropathy, affects 1 in 100-200 people in the UK. The condition, which is exacerbated by wheat, rye, barley and possibly oats, can be treated with a gluten-free diet in which these cereals are omitted. Serological screening, particularly of high-risk groups, with both IgA and IgG based systems can be used to identify cases. Diagnosis depends on the use of a small intestinal biopsy, which reveals the classical changes of loss of the normal villous architecture. Evidence suggests that gluten-sensitive T cells are involved in the pathogenesis of the disease. Use of in vitro systems has suggested an immuno dominant epitope within wheat gliadin, which has been shown to exacerbate the condition in vivo. This information can be used to devise strategies to develop immuno-modulatory peptides and cereals with the baking and nutritional qualities of wheat, rye and barley, but which do not exacerbate the condition.